RELIGIOUS EDUCATION AND THE CHALLENGE OF PLURALISM IN INDONESIA - Agus Nuryatno (Jurnal Pendidikan Islam, 2013)
This paper discusses the issue of religious education in relation to the challenge of religious pluralism in Indonesia. The focus of this paper is: On finding out the kind of religious education that is compatible with the challenge of religious pluralism? By employing concept of religious pluralism and theory of religious education, this paper argues that to face the challenge of religious pluralism it is necessary to change the model of religious education from in, to at and beyond the wall. Religious education in the wall contributes to shape an exclusive model of religiosity; while religious education at and beyond the wall contributes to shape an inclusive and pluralist model of religiosity. The last two models are compatible to be applied in Indonesia in order to face the challenge of pluralism, because both of them help students to accept, respect, and value religious differences. Religious education should show that the common enemy of religion is not people of different faiths, but poverty, corruption, violence, ignorance, and the like, and they have to stand together to fight against these true enemies.